Reflecting on the journey of environmental farm planning in New Zealand. Issue 3 (3rd July 2021) - Stokes, Simon; Macintosh, Katrina A.; McDowell, Richard W.
ABSTRACT: Environmental farm planning in New Zealand dates to the 1950s when soil conversation plans were first undertaken. Since then the extent and complexity of whole farm sustainability along with regulatory drivers and environmental compliance targets has increased. The public, and consumers, both domestically and internationally, are placing ever increasing demands and expectations on farmers to deliver high-quality produce with strong environmental values. Regulatory reform is challenging, with the details around the implementation process varying and far from clear. National-scale freshwater farm plans will be mandatory and enforceable in New Zealand within a few years. How this will deliver a clearer pathway to integrated resource management and provide the primary sectors with a tool to be world leaders in environmental management will depend upon plans being farmer centric and owned and adding value to their business.